Case report: A case of tibial tuberous osteochondroma complicated with gouty calculus - Qiang Zhang; Hongjiang Fu; Guomin Ye; Bin Deng; Qun Gao; Ya Chen (Frontiers in Oncology)
Osteochondroma (OC) mainly occurs in the metaphysis of long bones in children and adolescents, and it is extremely rare to occur in the tibial tuberosity and usually has no clinical symptoms. Here, we report a rare case of osteochondroma of the tibial tuberosity combined with gouty stones in a 44-year-old male patient who was found to have a mass on the left upper tibia for 20 years that had not been taken seriously or treated, and the patient was admitted to the hospital after the mass developed painful symptoms. In this case, X-ray examination clearly showed a lesion, which manifested as a limited bony protuberance with a wide base attached to the tibial tuberosity, and the imaging diagnosis was osteochondroma of the tibial tuberosity. The patient underwent surgical resection, and the pathologic results suggested that osteochondroma of the tibial tuberosity was combined with gouty stones. The patient’s symptoms improved significantly after the surgery, and no obvious discomfort or dysfunction has been found in the follow-up so far.